In situ reconstruction of ZIF-8 loaded on fibrous supports. Issue 37 (16th September 2021) - Song, Leilei; Li, Siqi; Li, Tao
Abstract : The fibre-supported ZIF-8 can undergo a full degradation–recrystallization cycle in a vapor phase with partial recovery of its porosity. Abstract : A simple solution casting technique was developed to load ZIF-8 particles on three commercially available fibrous supports. Benefiting from the open structure and high surface area of these fibrous networks, ZIF-8 particles can undergo a full cycle of degradation and recrystallization in a vapor-phase with 46% of their porosity recovered in the end.